Health-related Cognitive Factors and Intention to Adopt mHealth: The Mediating Influence of Attitude - Ahadzadeh, Ashraf Sadat; Ong, Fon Sim; Wu, Shin Ling (Makara Human Behavior Studies in Asia, 2023)
Mobile health (mHealth) is an important service that has remarkable effects on the development of the health care system. Health-related cognitive factors, such as perceived susceptibility (PSU), perceived severity (PSE), and health consciousness (HC), are associated with health-related technology adoption behavior. However, the underlying mechanisms of these associations have not been studied sufficiently. Attitude toward technology is a key construct in health psychology because it has a central role in motivating and changing behavior. Individuals’ attitude toward a particular behavior is expected to have a strong association with the behavior. This study aimed to examine how attitude toward mHealth plays a mediating role in the relationship between health-related cognitive factors (i.e., PSU, PSE, HC) and behavioral intention (BI) to adopt mHealth. A convenient sample of 374 Malaysian adults composed of 229 females and 149 males was recruited. These respondents completed a survey that measured PSU, PSE, HC, attitude toward mHealth, and BI to adopt mHealth. PSU and HC were significantly associated with BI to use mHealth, whereas PSE had no significant relationship with BI to use mHealth. Attitude toward mHealth mediated the relationship between two health-related cognitive factors (i.e., PSU and HC) and BI to adopt mHealth. The mediation results suggest that although BI to use mHealth is driven by health-related factors, it is facilitated by positive feelings toward health technology. Implications and recommendations for future research are presented.